2014
DOI: 10.3906/sag-1305-9
|View full text |Cite
|
Sign up to set email alerts
|

The expression of EGFR, cerbB2, p16, and p53 and their relationship with conventional parameters in squamous cell carcinoma of the larynx*

Abstract: IntroductionMany ions can be found in water as dissolved, absorbed/ adsorbed, or suspended matter, and the content of the ions determines whether the water is polluted. Some of the components in water can be recognized as exceeding safe limits or toxic. Wastes in open and partially enclosed quarries left behind after mining operations contain metals or toxic trace elements, and drainage waters that are rich in elements can mix into the surface water. These elements can be carried by acid water downstream and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Epidermal growth factor receptor (EGFR), a transmembrane tyrosine kinase receptor (TKR) of the ErbB family, is overexpressed or amplified in ~90% of HNSCC patients 219 , 220 and is associated with aggressive tumor behavior, 221 resistance to radiation, 222 and poor prognosis. 223 , 224 The constitutive activation of EGFR result in the activation of several downstream signaling pathways, including Ras/Raf/MAPK/ERK, PI3K/Akt, STAT, and the PLC-γ signaling pathways, 225 , 226 those are involved in proliferation, survival, CSCs maintenance 227 etc. While the relationship between HPV status, EGFR expression and patient outcome are still ambiguous in HNSCC, many studies have reported increased EGFR amplification in p16 −ve (a surrogate biomarker for HPV infection) oropharyngeal cancers.…”
Section: Targeting Hnscc Tme: Differential Response Among Hpv mentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR), a transmembrane tyrosine kinase receptor (TKR) of the ErbB family, is overexpressed or amplified in ~90% of HNSCC patients 219 , 220 and is associated with aggressive tumor behavior, 221 resistance to radiation, 222 and poor prognosis. 223 , 224 The constitutive activation of EGFR result in the activation of several downstream signaling pathways, including Ras/Raf/MAPK/ERK, PI3K/Akt, STAT, and the PLC-γ signaling pathways, 225 , 226 those are involved in proliferation, survival, CSCs maintenance 227 etc. While the relationship between HPV status, EGFR expression and patient outcome are still ambiguous in HNSCC, many studies have reported increased EGFR amplification in p16 −ve (a surrogate biomarker for HPV infection) oropharyngeal cancers.…”
Section: Targeting Hnscc Tme: Differential Response Among Hpv mentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is overexpressed in approximately 90% of HNSCC patients and is associated with the aggressive behavior of the cancer, resistance to radiotherapy, and a negative prognosis (91,92). The relationship between EGFR expression and HPV status of HNSCC tumors is not yet fully understood.…”
Section: Strategies To Fight Tme: Treatment Resistance In Head and Neck Cancersmentioning
confidence: 99%